PENGARUH METODE PEMBELAJARAN INKUIRI TERBIMBING TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN EKONOMI KELAS XII DI SMA NEGERI 1 SIANTAR - Sri Desra Damanik; Injen Pardamean Butarbutar; Debbi Petra Meyana Sitorus (JURNAL ILMIAH NUSANTARA, 2024)
The problem in this research is the low economic learning outcomes of students in the learning process. This research aims to determine the improvement in economic learning outcomes on the subject of class XII trading companies at SMA Negeri 1 Siantar for the 2023-2024 academic year by applying a guided inquiry learning approach.This type of research is Classroom Action Research which was carried out at SMA Negeri 1 Siantar. The research subjects were classes XII IPS 1 and XII IPS 2, totaling 59 people. The data collection technique in the research was a test to see student learning outcomes during the learning process. Data analysis techniques are carried out in several stages, namely data reduction, data presentation, and drawing conclusions.The learning outcomes of students in class and ???????????????????????? with N 69 of 1.995. Where ????ℎ???????????????????? ˃ ???????????????????????? then Ha is accepted. And the significant value of probability ˃ 0.05 with the Ha criterion is accepted, then hypothesis testing using both approaches obtains an acceptable Ha result.It can be concluded that by implementing a guided inquiry learning approach you can improve economic learning outcomes on the subject of trading companies in class XII of SMA Negeri 1 Siantar for the 2023 - 2024 academic year.